Detailed Investigation of Three-Dimensional Modeling and Printing Technologies From Medical Images To Analyze Femoral Head Fractures Using Finite Element Analysis - Çıklacandır, Samet; Mihçin, Şenay; Mihçin, Şenay; İşler, Yalçın (Elsevier, 2022)
Objectives: One of the fields, where additive manufacturing has numerous applications, is biomedical engineering. 3D printing is preferred over traditional manufacturing methodologies, mostly while developing subject-specific implants and medical devices. This study aims to provide a process flow detailing all the stages starting from the acquisition of radiological images from different imaging modalities; such as computed tomography (CT) and magnetic resonance imaging (MRI) to the printing of the bone morphology and finite element analysis; including the validation process. Materials & Methods: First, the CT scan of a lower abdomen area of a patient was converted into a 3D image using interactive medical imaging control system software. The segmentation process was applied to isolate the femoral head from the soft tissue and the pelvic bone. After the roughness errors and the gaps in the segments were removed using the 3Matic software, the file was converted to stereolithography (STL) file format to transfer to the 3D printer. The printing process was carried out via commercial powder-based Selective Laser Sintering (SLS) printer. The subject-specific femoral head model was formed in 3D. The Finite Element Analysis (FEA) of the femoral head was performed using a commercial FE software package. Results: The results show that experimental analysis and the CT scan-based FEA were compatible both for the stress distributions and the strain values as predicted by the models (R2=0.99). The deviation was calculated as approximately 12% between the experimental results and the Finite Element (FE) results. In addition, it was observed that the SLS technique produced useful results for modeling biomedical tissues with about 24x faster prototyping time. Conclusion: The prescribed process flow could be utilized in clinical settings for the pre-planning of the surgeries (≈428 minutes for femoral head) and also as an educational tool in the biomedical engineering field.
Keywords: Educational tools; Femoral head; Finite element analysis; Radiological images